2023
DOI: 10.1007/s00170-023-11701-w
|View full text |Cite
|
Sign up to set email alerts
|

Formation of highly ordered TiO2 nanotubes on Ti6Al4V alloys manufactured by electron beam powder bed fusion (E-PBF)

Abstract: Highly ordered TiO2 nanotubes were obtained by anodization on Ti6Al4V substrates manufactured by electron beam powder bed fusion (E-PBF). Effects of anodization parameters such as anodizing time, stirring, fluoride concentration, and water content were analyzed in an organic electrolyte (ethylene glycol) that contains ammonium fluoride. The ordering of the nanotubes was measured by regularity ratio calculations based on fast Fourier transform (FFT) from SEM images. It was found that for the processed specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
1
0
0
Order By: Relevance
“…This has been observed both on the naturally occurring thin passive film that spontaneously forms on the surface of the alloy [90] as well as on thick flat anodic oxides [91,92]. However, the anodic tubular layer of the samples used in this study presents V-doped TiO 2 nanotubes, as shown in Figure 1, in accordance with the findings of a previous work [44] later corroborated by others [93]. It is possible that when immersed in cell culture media, V-doped heat-treated anodic oxide preferentially corrodes versus the Al-doped oxide, either due to its stability inherent to the chemical composition or due to a synergistic effect of the recrystallization after heat-treatment, which could have further stabilized the Al-doped oxide.…”
Section: Cytocompatibility Evaluation and Ion Releasesupporting
confidence: 90%
“…This has been observed both on the naturally occurring thin passive film that spontaneously forms on the surface of the alloy [90] as well as on thick flat anodic oxides [91,92]. However, the anodic tubular layer of the samples used in this study presents V-doped TiO 2 nanotubes, as shown in Figure 1, in accordance with the findings of a previous work [44] later corroborated by others [93]. It is possible that when immersed in cell culture media, V-doped heat-treated anodic oxide preferentially corrodes versus the Al-doped oxide, either due to its stability inherent to the chemical composition or due to a synergistic effect of the recrystallization after heat-treatment, which could have further stabilized the Al-doped oxide.…”
Section: Cytocompatibility Evaluation and Ion Releasesupporting
confidence: 90%